SOSIALISASI PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DI DESA TLAHAB KECAMATAN KARANGREJA KABUPATEN PURBALINGGA - Elly Kristiani Purwendah; Aniek Periani; Agoes Djatmiko (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
This community service aims to provide motivation to the people of Tlahab Village, Wanareja District, Purbalingga Regency to carry out waste management with an awareness of good and healthy environmental insight as a right and obligation as citizens and carry out waste sorting methods so that they become efficient, provide economic value as well as developing the circular economy concept as a goal of sustainable development as one of the environmental principles and the main rationale for waste management in Indonesia.